Broad‐Spectrum Photodetection with High Sensitivity Via Avalanche Multiplication in WSe2. Issue 22 (22nd August 2022) - Choi, Haeju; Choi, Seunghyuk; Kang, Taeho; Son, Hyeonje; Kang, Chanwoo; Hwang, Euyheon; Lee, Sungjoo
Abstract: High‐sensitivity broad‐spectrum photodetectors with detection capabilities ranging from ultraviolet to infrared have attracted significant attention for their application as photodetectors. They can be used as a receiver for all applications in optical communication for covering a wide spectral range with a single photodetector, which can significantly lower the overall system cost. In this study, by constructing an avalanche photodetector (APD) fabricated with 2D WSe2, a high photoresponsivity of over 10 7 A W −1 for a broad spectrum of 405–1310 nm is achieved under an electric field higher than the critical field for the avalanche multiplication of 35 kV cm −1, overcoming the limitation of the detectable wavelength induced by the energy bandgap of the material. The benchmark in terms of the photocurrent‐to‐dark current ratio and responsivity over a wide wavelength range demonstrates that the fabricated WSe2 APD outperforms the reported 2D layered material‐based APDs and reported WSe2 photodetectors. The obtained results can be attributed to the high‐gain mechanism via avalanche multiplication and phonon‐assisted photogeneration in WSe2, enabling efficient photodetection beyond sub‐bandgap wavelengths. This result provides a promising general approach for developing a single photodetector that can cover a broad spectral range with a high sensitivity for future optical communication. Abstract : Broad‐spectrum photodetection with high sensitivity is demonstrated by constructing an avalanche photodetector fabricated with 2D WSe2 . High photoresponsivity of over 10 7 A W −1 for a broad spectrum of 405–1310 nm is achieved under an electric field higher than the critical field, overcoming the limitation of the detectable wavelength induced by the energy bandgap of the material.